Oxidative Stress and Acute-Phase Response Status During Treatment in Premature Calves with Respiratory Distress Syndrome - OK, M; YILDIZ, R; TRAŞ, B; COSKUN, P; AKAR, A (Journal of the Hellenic Veterinary Medical Society, 2021)
This study aimed to determine lipid peroxide (LPO), antioxidant capacity (AOC), and acute-phase protein changes before and after different nebulization treatments in premature calves with respiratory distress syndrome (RDS). Thirty-six premature calves were divided into equal number of 6 groups. Group 1 was labelled as negative control and received standard treatment. Group 2 was labelled as positive control; Groups 3, 4, 5, and 6 were labelled as trial groups. These groups received nebulizer treatment. Nebulizer drug combinations were as follows: Group 2 (fluticasone), Group 3 (formoterol + fluticasone), Group 4 (ipratropium bromide + fluticasone), Group 5 (fluticasone + furosemide) and Group 6 (formoterol + ipratropium bromide + furosemide + fluticasone). Venous blood was taken from all calves before (0 hour) and after treatment (24th, 48th, 72nd hour). It was concluded that total LPO levels gradually decreased while AOC levels increased during treatment but there was no difference in the serum amyloid A (SAA) and fibrinogen levels within groups. In conclusion, supportive and nebulizer treatments to improve function of lungs were demonstrated to alleviate oxidative stress. However, in order to reveal the effects of local nebulizer applications on oxidative stress, further studies are required to investigate oxidation parameters in the bronchoalveolar fluid.